Burnout syndrome among health care workers in Hungary – a literature review - Kocsicska, Ivana (METSZETEK Társadalomtudományi Folyóirat, 2022)
Burnout is recognised as an occupational hazard and prolonged response to chronic interpersonal stressors at work in various people-centred professions, with higher prevalence among health care workers. The main objective of this research was the integrative review of the literature on burnout syndrome in Hungarian health care workers. Twelve (12) studies found in PubMed database were included in the research and a number of important conclusions have been summarized about burnout syndrome among employees of the Hungarian health care system. Also, as important conclusion it has been highlighted, that recognising, preventing, and treating burnout and depression among health care workers should be one of the priorities of the health care in Hungary.